Remodeling of Rat M. Gastrocnemius Medialis During Recovery From Aponeurotomy - Rivares, Cintia; Brunner, Reinald; Pel, Johan J. M.; Baan, Guus C.; Huijing, Peter A.; Jaspers, Richard T. (Frontiers in Physiology, 2020)
Aponeurotomy is a surgical intervention by which the aponeurosis is halfway transsected perpendicular to its length. This principle applies also to intramuscular lengthening and fibrotomia. In clinics, this intervention is performed in patients with cerebral palsy in order to lengthen or weaken spastic and/or short muscles. Due to proximal aponeurotomy, muscle fibers located distally from an aponeurosis gap that develops, lose myotendinous connection with the origin. During recovery from this intervention, new connective (scar) tissue restores the gap in the aponeurosis and within the muscle. As a consequence the aponeurosis is longer during and after recovery. In addition, the new connective tissue is more compliant than regular aponeurosis. The aim of this study was to investigate changes in muscle geometry and adaptation of the number of sarcomeres in series after recovery from aponeurotomy of the proximal gastrocnemius medialis (GM) aponeurosis and relate these results to possible changes in the muscle length-force characteristics. Aponeurotomy was performed on the proximal aponeurosis of rat m. GM, and followed by six weeks of recovery. Results were compared to muscles of the control group and those of a sham operated group. After recovery from aponeurotomy, proximal and distal muscle fiber lengths were similar to that of control group. The fiber mean sarcomere length from fibers located proximally relative to the aponeurosis gap could not be shown to be significantly different. In contrast fibers located distally showed a 16-20% lower mean sarcomere lengths at different muscle lengths. The serial number of sarcomeres within the proximal as well as distal muscle fibers were unchanged. After recovery, muscle length-force characteristics were similar to those of the control group. A reversal of proximal-distal difference of fibers mean sarcomere lengths within muscles during recovery from aponeurotomy is hypothesized to cause such a net effect. These results indicate that after recovery from aponeurotomy, the muscle function was preserved by geometrical adaptations. Moreover, it seems that the generally accepted rules of adaptation of serial sarcomere numbers are not applicable in this situation.